Creativity in museum practice - Norris, Linda; Tisdale, Rainey (Walnut Creek, California : Left Coast Press, 2014)
"With this book museum professionals can learn how to unleash creative potential throughout their institution. Drawing from a wide range of research on creativity as well as insights from today's most creative museum leaders, the authors present at a set of practical principles about how museum workers at any level--not just those in "creative positions"--can make a place for creativity in their daily practice. Replete with creativity exercises and stories from the field, they guide readers in developing an internal culture of creative learning, as well as delivering increased value to museum audiences"--
Introduction: Why creativity matters in museum work -- Your creative practice -- Building creative cultures -- A field-wide creative infrastructure -- Creative museums, creative communities -- Afterword: Our creative process -- Pocket guide to creativity in museum practice -- The get going game.
Includes bibliographical references (pages 221-236) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Museum techniques -- Social aspects; Creative thinking; Electronic books